2015
DOI: 10.17576/jsm-2015-4410-02
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Model to Predict Wellbore Fracture Pressure with Acid Damage

Abstract: Hydraulic fracturing becomes more difficult when confronted with a formation of high fracturing pressure. In such formations, acidizing before the main fracturing treatment provide a method to reduce fracture pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Youliang Chen and Peng Xiao studied the damage constitutive model of rocks under freeze-thaw-confining pressure and acid erosion and found the damage evolution of rock under acid erosion and freezing-thawing and confining pressure, and derived the model parameters to reveal the reliability of the model [8] . Fanhui Zeng provided a method of acidifying rocks to reduce fracturing pressure, and the research results showed that acidification can reduce rock strength and critical stress intensity factor of cracks, thereby reducing crack pressure combination [9] . Jianchun Guo found through quantitative prediction models that the greater the acid concentration, the greater the rock damage variables and shear strength intensity [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Youliang Chen and Peng Xiao studied the damage constitutive model of rocks under freeze-thaw-confining pressure and acid erosion and found the damage evolution of rock under acid erosion and freezing-thawing and confining pressure, and derived the model parameters to reveal the reliability of the model [8] . Fanhui Zeng provided a method of acidifying rocks to reduce fracturing pressure, and the research results showed that acidification can reduce rock strength and critical stress intensity factor of cracks, thereby reducing crack pressure combination [9] . Jianchun Guo found through quantitative prediction models that the greater the acid concentration, the greater the rock damage variables and shear strength intensity [10] .…”
Section: Introductionmentioning
confidence: 99%